A Survey on Fake News Detection - Naveen Kumar Reddy, Sireddy.; M., Sujatha (International Journal of Psychosocial Rehabilitation, 2020)
Social media is a double-edged sword for news consumption; on one side it is easy to access and low cost, and on the other side fake news will spread widely and include false information. The wide spread of this fake news results in negative impacts on society and individuals. Fake news is mainly created to misguide readers in order to believe information that is not true. Source, headline, body text, and image or video are the content attributes for news. Source is the news article publisher. The short text that makes readers attention and describes the important topic in that article is called  the headline. The entire content about that article is present in body text and includes images or videos that are related to that article. Based on these attributes, fake news characteristics are extracted.